2001
DOI: 10.1152/jn.2001.86.2.809
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Pavlovian Conditioning Effects on the Brain: Blocking, Contiguity, and Excitatory Effects

Abstract: Pavlovian conditioning effects on the brain were investigated by mapping rat brain activity with fluorodeoxyglucose (FDG) autoradiography. The goal was to map the effects of the same tone after blocking or eliciting a conditioned emotional response (CER). In the tone-blocked group, previous learning about a light blocked a CER to the tone. In the tone-excitor group, the same pairings of tone with shock US resulted in a CER to the tone in the absence of previous learning about the light. A third group showed no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 60 publications
3
36
0
Order By: Relevance
“…This effect is similar to what was found in the present study and may reflect the decrease in signal value of a non-meaningful stimulus. Our study on the blocking effect (Jones and Gonzalez-Lima, 2001b) revealed excitatory effects in the accumbens and CS-US contiguity effects in rCA1, Per, and AC. The present study continues to emphasize the importance of hippocampal and parahippocampal regions in converging auditory (CS) and somatosensory (US) information.…”
Section: Discussionmentioning
confidence: 57%
“…This effect is similar to what was found in the present study and may reflect the decrease in signal value of a non-meaningful stimulus. Our study on the blocking effect (Jones and Gonzalez-Lima, 2001b) revealed excitatory effects in the accumbens and CS-US contiguity effects in rCA1, Per, and AC. The present study continues to emphasize the importance of hippocampal and parahippocampal regions in converging auditory (CS) and somatosensory (US) information.…”
Section: Discussionmentioning
confidence: 57%
“…Over the years, the technique has been extensively used to unravel the involvement of specific brain areas in several paradigms involving somatosensory activation through various modalities (Coopersmith and Leon, 1984;Kennedy et al, 1976;Melzer et al, 1985;Schwartz et al, 1979). Furthermore, it has been applied to obtain functional maps of learningrelated activity such as in Pavlovian conditioning (Jones and Gonzalez-Lima, 2001), habituation (Gonzalez-Lima et al, 1989;Toga and Collins, 1981), or different working memory tasks (Friedman and Goldman-Rakic, 1988;Sybirska et al, 2000). The technique also offers the possibility to study the dynamic changes in the activation of a particular area along the different phases of a learning process.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, subjects were exposed to an hour-long 5 seconds on, 1 second off CS tone. This repeated frequency of tone presentations has been determined from previous FDG studies to produce optimal CSevoked buildup of FDG for mapping the regional effects of the tone in the brain (Jones and Gonzalez-Lima, 2001). The change in tone duration did not affect the level of freezing of animals, as verified by the level of freezing observed after the FDG injection.…”
Section: Training Proceduresmentioning
confidence: 99%
“…FDG uptake was quantified by film densitometry as described previously by Jones and Gonzalez-Lima (2001). Briefly, developed films were placed on a light box and optical density of images was captured by the video camera.…”
Section: Image Analysismentioning
confidence: 99%